Information and Data Distribution System for Rural Areas of Indonesia - Amron, Kasyful; Basuki, Achmad; Pramukantoro, Eko Sakti; Yahya, Widhi (Faculty of Computer Science (FILKOM) Brawijaya University, 2016)
Abstract. Internet becomes critical infrastructure in the distribution of information. The information is used for decision making and ensure the success of human activities. However, the distribution of information in rural Indonesia is inconvenient, because the digital communication infrastructure (internet) doesn’t cover all areas in Indonesia. This problem causes the digital divide in Indonesia. This study proposes communications infrastructure and data transfer mechanism or media sharing that can be applied to a variety of rural areas conditions in Indonesia, which has limited communications infrastructure. The approach is to build low power digital carrier devices in the form of minicomputer and utilize Delay or Disruptions Tolerant Network (DTN) architecture. Testing results in the digital carrier node show that the data is successfully delivered. Keywords: Rural Area, Mini-PC, Delay Tolerant Network